The amendment of the law in Ireland as to maintenance of illegitimate children - Lawson, William (Statistical and Social Inquiry Society of Ireland, 1914)
The statute law in force in Ireland differs in many respects from that in force in England, and there are many Acts- of Parliament, which apply to England only, which might with advantage be extended to Ireland. One of these differences is to be found in the law as to the liability of a father to maintain his illegitimate child.
Read May 8th, 1914
Keywords: Illegitimacy; Family law; 314.15